2012
DOI: 10.1016/s1514-0326(12)60002-6
|View full text |Cite
|
Sign up to set email alerts
|

Leisure and the Net Opportunity Cost of Travel Time in Recreation Demand Analysis: An Application to Gros Morne National Park

Abstract: Using count data models that account for zero-truncation, overdispersion, and endogenous stratification, we estimate the value of access to recreational parks. The focus is on the empirical estimation of the proportion of the wage rate that best approximates park visitors' opportunity cost of travel time within the cost of their trip and its effects on estimated consumer surplus. The fraction of hourly earnings that corresponds to the opportunity cost of travel time is endogenously estimated as a function of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 34 publications
0
17
0
2
Order By: Relevance
“…Apart from convenience, this property contributes to make TCM benefit estimates susceptible of being, in part, artefacts of arbitrary accounting conventions.4 For a recent review of the literature, seeAmoako-Tuffour and Martínez-Espiñeira (2008).…”
mentioning
confidence: 99%
“…Apart from convenience, this property contributes to make TCM benefit estimates susceptible of being, in part, artefacts of arbitrary accounting conventions.4 For a recent review of the literature, seeAmoako-Tuffour and Martínez-Espiñeira (2008).…”
mentioning
confidence: 99%
“…In future research, the trade-offs between planning policies and actions identified through differences in the provision of categories of ESs should be qualified in terms of losses and gains in the supply of land uses rather than of land covers, since the intensity of management and the production of wealth can only be identified through land uses, which CORINE-like spatial taxonomies do not capture. Another relevant issue that needs to be addressed is the relationship between planning policies and measures and the resulting visual landscape, which plays an important role in shaping the attractiveness of spatial contexts [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…RecVal is calculated on the basis of geotagged information retrieved from the social media Flickr, representing the attractiveness of a certain area to visitors in a defined time period. Several studies [50][51][52] show that recreational attractiveness of an area, conceived of as the demand for recreational activities, is influenced by different factors, such as accessibility and accommodation availability. Therefore, a possible recommendation concerns making these areas more accessible through infrastructures that, on the one hand, support slow mobility (such as cycle and pedestrian paths) and, on the other hand, do not increase habitat fragmentation.…”
Section: Discussionmentioning
confidence: 99%